Modelling shock waves in composite materials using generalised orthotropic pressure - Mohd Nor, M. K.; Ho, C. S.; Ma’at, N.; Kamarulzaman, M. F. (Springer, 2020)
Excellent mechanical properties of composite materials have numerous engineering applications, especially in aerospace structures. The main characteristics are due to their strength-to-weight ratio and lowcost of manufacturing. Therefore, the understanding and an ability to predict the formation and propagation of shock waves in such materials are important. This paper investigates the ability of the constitutive model generalised for orthotropic materials to predict a complex elastoplastic deformation behaviour which involves very high pressures and shockwaves in composite materials. The formulation consists of a stress tensor formulated based on the combination between Mandel stress tensor and a new pressure generalised for orthotropic materials. The formulation is further combined with a shock equation of state (EOS) to define a new orthotropic EOS. The implementation of this newly orthotropic EOS in the Laboratory (LLNL)-DYNA3D code of UTHM’s version is presented in this paper for potential implementation in the other hydrocode. The formulation is then tested against plate impact test data of carbon fibre-reinforced epoxy composites along the through-thickness and longitudinal directions including the results obtained by Vignjevic’s model (Vignjevic et al. in J Appl Phys 104(4):044904, 2008). A good agreement is obtained in each test.